Pengembangan Media Pop Up Book pada Pembelajaran IPA Materi Daur Hidup Hewan di Kelas IV SD Negeri 106814 Tembung - Nur, Ovi Ocvrianda; Sujarwo, Sujarwo (Indonesian Research Journal on Education, 2022)
This study aims to develop a Pop Up Book in science lessons on animal life cycle material forfourth grade elementary school. Pop Up Book media to make it easier for students to understand science learning material for animal life cycles. This research belongs to the type of research and development R&D (research and development) with the ADDIE model, namely analysis, design, development, implementation, evaluation. Data collection through observation, product design using the Canva application. The evaluation of the Pop Up Book product was validated by media and material experts, namely two lecturers at the Muslim Nusantara University Al-Washliyah Medan and interviews with fourth grade elementary school teachers. The results of the assessment from the validation stage are used as material for revising the Pop Up Book . The results showed that the validation results by material and media expert validators as well as interviews with teachers about the Pop Up Book media for learning science on animal life cycle materials were included in the "good" category and were suitable for use. Thus, the development of Pop Up Book media in science lessons for grade IV SD is suitable for use by schools, teachers, and students.